LED street lighting best practices. (Asian Development Bank, 2017)
Providing street and public lighting can account for up to 38% of energy consumption and greenhouse gas emissions in some cities. New energy efficient technologies and design can cut street lighting costs dramatically (up to 60%) and reduce greenhouse gas emissions by the same amount. These savings can reduce the need for new generating plants and redeploy scarce capital to delivering energy access to populations in remote areas. The savings also allow municipalities to expand street lighting coverage to additional areas that include low income and other underserved areas.